Potensi dan Tantangan Penerapan Platform Crowdfunding Donasi Berbasis Blockchain - Muhammad Rizky; Teduh Dirgahayu (Universitas Serang Raya, 2025)
The generosity of Indonesian society, influenced by tradition and religion, has continued to grow with the convenience of digital facilities for crowdfunding. However, there are still challenges to be addressed, such as accountability and transparency in the use of donated funds. The emergence of blockchain technology offers opportunities to enhance transparency, security, and efficiency in fundraising. This study aims to evaluate the potential and challenges of implementing blockchain-based donation crowdfunding platforms through a systematic literature review (SLR) approach following the PRISMA protocol. From the analysis of 41 articles, 37 blockchain-based crowdfunding platforms were found to have the potential to improve transparency, trust, efficiency, accountability, and reduce transaction costs. The main challenges faced include scalability, regulatory compliance, privacy concerns, user adoption, and integration with existing systems. The findings of this study provide valuable insights for nonprofit organizations and philanthropic institutions in leveraging blockchain technology for donation crowdfunding.